The institutional dynamics of fear. Police (sexual) violence against policewomen - Sirimarco, Mariana (Revista de Antropología Social, 2022)
Fear is a key element in the accounts made by Argentinean policewomen that have suffered from sexual violence (harassments, abuses, rapes). This paper turns fear into an underlying theme between two related spheres. The first one, connected to the ways in which fear is individually experienced. The second one, related to the institutional weave that produces it and supports it. The aim of this paper is therefore dual: to highlight some ways fear may take in the accounts of these women, and to enlighten the features that link this fear to a specific context. What does the fear of these policewomen say about police institution?